Engineering Department at Dow Chemical Company - Dow Chemical Company (1952)
General view of employees at work in the Engineering Department at the Dow Chemical Company's headquarters in Midland, Michigan. Assorted blueprints and papers are visible on the drafting tables arranged throughout the room. The Engineering Department commonly focused on designing and implementing projects of varying sizes, including the construction of new chemical manufacturing plants and support facilities, as well as improving the effectiveness and efficiency of existing assets.
Keywords: Engineering; Engineers; Employees; Dow Chemical Company